Perlindungan Hukum Pejuang Lingkungan Berdasarkan Pasal 66 UU PPLH dalam Kasus Penangkapan Dera dan Munif di Jawa Tengah - Rayi Kharisma Rajib; Fairusna Chalisa Alya; Siti Fatimah Azzahra (Jurnal Ilmu Sosial dan Humaniora, 2026)
Article 66 of Law Number 32 of 2009 concerning Environmental Protection and Management provides legal protection for environmental defenders from criminal prosecution and civil lawsuits. However, its implementation still faces challenges in law enforcement practices. This study discusses the effectiveness of Article 66 of the Environmental Protection and Management Law in the case of the arrest of two environmental activists in Semarang in November 2025. The research uses a normative legal method with statutory and case approaches. The results show that legal protection for environmental defenders has not been fully effective because law enforcement officials tend to focus on criminal allegations without considering the context of environmental advocacy. Therefore, a more consistent implementation of the Anti-SLAPP principle is needed to ensure effective legal protection for environmental defenders.